Rowing Between Scylla and Charybdis: Income Transitions in Central European Households - Barbara B. Torrey; Timothy Michael Smeeding; Debra Bailey (Luxembourg Income Study (LIS), 1995)
This paper examines household level economic changes in Central and Eastern Europe before and during the transformations of their economies. The authors test the assumptions that the economic transitions would increase poverty and income inequality within the Czech Republic, Slovak Republic, Hungary, and Poland, and that vulnerable populations would bear a disproportionate burden of the economic decline. The data suggest that while Central European economies suffered rapid declines, the poverty rates of individuals increased only slightly. A simulation of the effects of adding the informal economy on the income distribution in Hungary showed some changes in inequality calculations while aggregate consumption patterns showed increases in consumption of durables and luxury goods. The adverse effects of macroeconomic decline were thought to be buffered by government social policy and other household coping behavior.
Keywords: 330; Einkommensverteilung; Armut; Systemtransformation; Polen; Tschechische Republik; Ungarn